PENGARUH JENIS BAHAN LITTER TERHADAP GAMBARAN DARAH BROILER YANG DIPELIHARA DI CLOSED HOUSE - Miranti Olivia; Madi Hartono; Veronica Wanniatie (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The aim of the research was to : (1) knowing blood descriptions (red blood cell, white blood cell, andhaemoglobin) of broiler at closed house with kind of litter material, and (2) finding the best litter for broilerblood descriptions at closed house. The research was conducted during 26 days since April 16, 2014 to May10, 2014 at the PT Ramajaya farm’s on Krawangsari village, sub District Natar, South Lampung District.The chicken used was broiler strain cobb with trademark CP 707 product by PT. Charoen pokphandIndonesia tbk for 270 chicken. Broiler start to get handling between age of 14 and 26 days. The researchmethod was experimentally with Completely Randomized Design (CRD) were divided into 3 treatments andrepeated for 6 times, that is p1: rice hull; p2 : wood shavings; p3 : straw. The data were analysis withAnalysis of Variance and if it shows 5%. The result indicated that the treatmentis : (1) litter from rice hull,wood shavings, straw did not have significant effect (P>0,05) on red blood cell, white blood cell andhaemoglobin of broiler. Litter rice hull, wood shavings and straw are good for broiler maintained at closedhouse.